"This is a story of who America is": Cultural memories and black civic identity. Issue 2 (3rd May 2020) - Elizabeth Vickery, Amanda
Abstract: In this study the author explores how an African American woman and elementary teacher utilized her family's history and cultural memories during the Great Migration to reconsider how we (re)member the past and understand what it means to be a citizen. The researcher found that the participant viewed migration as a central theme in understanding Black civitas and used her family's stories as a way to reinsert diverse bodies into the U.S. civic curriculum. Moreover, the participant was able to understand teachers can use their experiences to create a curriculum filled with lived experiences as a healing space. Implications from this study demonstrates the necessity of teaching difficult histories as well as decentering whiteness, in terms of teaching and research, in order to embrace endarkened and Black feminist ways of knowing.